Strategi Pemertahanan Bahasa Sunda Lea Indramayu - Dede Endang Mascita; Sariah Sariah; Siwi Susilowati (Badan Pengembangan dan Pembinaan Bahasa, 2021)
This study aims to describe the efforts to maintenance Lea (Lelea) Sundanese language in Lelea Village, Indramayu. Lea Sundanese language is a different Sundanese language when compared to the main Sundanese in the Priangan area. The focus of this research is how to maintenance Lea Sundanese between the use of the Dermayon Javanese language that developed in the Indramayu region and Indonesian as the national language. This study seeks to describe the data and facts that the efforts to maintain the Sundanese Lelea language both in the form of language use in the language activities of the community, as well as policies issued by the local village government relating to the use of language as a means of communication between residents. Based on the results of the analysis of the data obtained it was concluded that Lea Sundanese is one of the regional languages formed from Sundanese and Javanese Dermayon (Indramayu). In their efforts to keep them prisoner, the community and village government carry out language socialization such as: 1) in religious activities: recitation and Friday sermons; 2) education: KBM in schools and madrasah; 3) village government services: meeting activities, counseling to residents; 4) culture: celebrations of traditional events, for example: Ngarot and marriage; 5) PKK: mothers' social gathering; and 6) youth: youth program.AbstrakBahasa Sunda Lelea merupakan bahasa Sunda yang berbeda apabila dibandingkan dengan bahasa Sunda utama yang berada di daerah priangan. Fokus penelitian ini adalah bagaimana pemertahanan bahasa Sunda Lea di antara penggunaan bahasa Jawa Dermayon yang berkembang di wilayah Indramayu, dan bahasa Indonesia. Penelitian ini berusaha mendeskripsikan data dan fakta upaya pemertahanan bahasa Sunda Lelea baik berupa penggunaan bahasa dalam kegiatan berbahasa masyarakatnya, maupun kebijakan-kebijakan yang dikeluarkan pemerintah desa setempat berkaitan dengan penggunaan bahasa sebagai alat berkomunikasi antarwarga. Penelitian ini menggunakan metode deskriptif kualitatif. Berdasarkan hasil analisis terhadap data yang diperoleh, disimpulkan bahasa Sunda Lea adalah salah satu bahasa daerah yang terbentuk dari bahasa Sunda dan bahasa Jawa Dermayon (Indramayu). Dalam upaya pemertahanannya, masyarakat dan pemerintah desa melakukan sosialisasi bahasa seperti: 1) dalam kegiatan keagamaan: pengajian dan khutbah Jumat; 2) pendidikan: KBM di sekolah umum dan madrasah; 3) pelayanan pemerintahan desa: kegiatan rapat, penyuluhan ke warga; 4) kebudayaan: perayaan acara adat, misalnya upacara Ngarot dan pernikahan; 5) PKK: arisan ibu-ibu; dan 6) kepemudaan: acara karang taruna.